(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article explores the topic’s importance in light of how the digital economy has impacted many aspects of our lives and how information and communication technologies are developing and becoming more widely used. The article also includes information on the fundamentals of the digital economy.